Implementasi Manajemen Kurikulum Merdeka Belajar dalam Meningkatkan Kompetensi Siswa SMK Budi Utomo Binjai - Rini Yani; Sri Nurabdiah Pratiwi; M. Isman (UMSU, 2023)
The purpose of this study was to find out how the planning, implementation and evaluation of the independent learning curriculum at Budi Utomo Binjai Vocational School and the level of effectiveness of implementing the independent learning curriculum management in increasing the competency skills of graduates in the industrial world. The research approach is a qualitative and quantitative embedded type, namely a qualitative approach as the primary method and quantitative as a secondary method. The research respondents were school principals, teachers and students at SMK Budi Utomo Binjai. The data collection tools are interviews, documentation and observation and questionnaires. The results of the research on independent learning curriculum planning and industrial work practices at Budi Utomo Binjai Vocational School were carried out at the beginning of the new school year, when class XI (semester 3 or 4) carried out internships. Then the planning for class X has been prepared. The school had a little difficulty with adding the practice time to 6 months, and having difficulty arranging the practice places proposed by students, if the places were too far away. Some of the activities in planning industrial work practices are needs analysis, industry mapping, outreach, selection of practice places and tutors, and debriefing. In addition, the implementation of the independent learning curriculum and industrial work practices at Budi Utomo Binjai Vocational School is carried out according to the schedule and the results of the agreement from the industry, which is approximately 6 months or 1 semester. However, schools have difficulty handing over, monitoring, and withdrawing students whose internship places are outside North Sumatera, this is due to factors of cost, distance, and time. Likewise, the evaluation of the independent learning curriculum and industrial work practices at Budi Utomo Binjai Vocational School was carried out by collecting data and analyzing it. Each department will report the results of their students' internships. The evaluation went according to the agenda, but in the evaluation activities the industry was not involved, this was because the school felt that the responsibility of the industry had been completed after the students withdrew from their practice place. In general, the implementation of independent learning curriculum management at Budi Utomo Binjai Vocational School in supporting the competence of graduates in the industrial world is very effective or 87% of respondents said it was very good.